PRINCIPLES OF SOCIO-CULTURAL IDENTITY OF THE MODERN ARCHITECTURAL ENVIRONMENT - Абизов, В. А. (Art and Design, 2018)
Investigation and identification of hierarchical levels of manifestations and signs of socio-cultural identity (ethnіс design) of the architectural environment and the corresponding system and structural foundations of its formation and development. The study is based on a system approach that allows us to consider the architectural environment as a hierarchically subordinate integrity of open and closed spaces. Were used also the methods of historical, comparative and typological analysis, method of observation of architectural objects. Results. The principles of socio-cultural identity of the modern architectural environment are determined. Hierarchical levels of forming the architectural environment are the next: social, urban, functional, compositional and spatial, subject-spatial arrangement of environment, synthesis of arts, appropriative building materials and products. Scientific novelty consists in determination of methodological principles of formation and development of the phenomenon of ethnic design of architectural environment at different hierarchical levels.